El impulso del turismo alternativo en Uruguay: la experiencia del proyecto Uruguay Alternativo - Juan Andrés Pardo (Études Caribéennes)
The “sun and beach” has been during decades the main product of uruguayan tourism. Nervertheless, the above mentioned country possesses certain characteristics that make it inclined for the development of alternative tourism, which is unknown today and which has not attracted State's interest so far.This present article raises an approximation to the reality of this tourism in Uruguay, Uruguay Alternativo" based on the experience arisen on 2012.